Hemorrhagic shock due to irreducible uterine torsion in a third trimester twin pregnancy: A case report - J, Darido; J, Grevoul Fesquet; J, Diari; C, El Haddad; N, Bouzid; N, Abou El Hassan; L, Khadam; L, Rigonnot (Clinical Journal of Obstetrics and Gynecology, 2020)
Uterine torsion is a rare life-threatening event that happens at any age or any gestational age. By definition, it consists of a rotation of more than 45 degrees around the long axis of the uterus. The reported cases have variable presentations. The uterine torsion can happen without any sequelae either for the fetus or the mother. However, fetal and maternal mortalities were also reported in such a case. We hereby, report the case of a 29-year-old female patient, with previous four Normal Vaginal Deliveries, pregnant with twins, presenting at 36 weeks gestation with an irreducible uterine torsion at the third trimester of her pregnancy complicated by maternal and fetal deaths. We concluded that the prognosis is improved as long as the management is done rapidly. More data is needed to know about the genetic predilection and the characteristics of imaging workup for a rapid preoperative diagnosis of this condition.